Integration of IoT in Wearable Devices for Health Monitoring: Challenges and Potentials in the Field of Electrical Engineering - Pratolo Rahardjo (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The Internet of Things (IoT) has become a major driver in technological transformation, including in wearable devices for health monitoring. The background of this research is based on the increasing need for a real-time, effective, and data-driven health system. The purpose of this study is to explore the challenges and potential of IoT integration in wearable devices, especially in the field of electrical engineering. The method used is a literature study with a content analysis approach to identify patterns and themes from related academic sources between 2018 and 2023. The results show that IoT-based wearable devices can improve the quality of healthcare by integrating sensor technology, communication modules, and artificial intelligence. However, some significant challenges, such as data security, energy consumption, and device interoperability, need to be addressed to drive widespread adoption of the technology. Blockchain is proposed as a potential solution to security concerns, while 5G offers greater bandwidth for data efficiency. This study provides important insights for the development of IoT-based wearables as a key element in modern health management.